Development of mini encylopedia on solar system / Noorshida Amir - Amir, Noorshida (2006)
An electronic multimedia encyclopedia can present information in better ways than a traditional encyclopedia. When interactivity is built into multimedia, control is given to the user. Thus, this interactivity facilitates the user on searching their information s as interactive as multimedia encyclopedia. The user has more fun and learns fast. For instance, an article on World War II can include hyperlinks of countries involved in the war. When a user clicks on a hyperlink, user is redirected to a detailed article about that coimtry. In addition, it can include a video on Pacific Campaign. It can also present images which are maps pertinent to World Warn.